(untitled) (Bioagro, 2020)
Currently, blueberry represents one of the fruits with the greatest projection; however, its production depends on its ability to adapt to management practices and cultivation areas. The purpose of this study was to evaluate the agronomic behavior of four varieties of blueberries (Vaccinium corymbosum L.) grown on three substrates and three altitudinal zonations. The experiment was carried out under a completely randomized block design with factorial arrangement of treatments (variety x substrate). The study was independently established in three locations with altitudes ranging between 2000 and 3000 meters above sea level. The obtained data was subjected to Anova and Tukey test. The results showed significant differences among levels of the two factors, but without interactions between them. Biloxi variety showed greater height, branching and yield in the different establishment areas. On the other hand, the branching capacity was significantly higher in plants established on a substrate composed of pine peat+forest peat+sandy-loam soil. The findings provide information about adaptability and production of the evaluated varieties.